The Effect of Physical Activities and Strength Exercise to Proprioseptive Stimulation on Life Quality Improvement in Elderly - Loriana, Rina; Andi, Parellangi (Journal of Global Research in Public Health, 2019)
Background: The increase of life expectancy is one indicator of public health, especially in Indonesia. The elderly in Indonesia in 2020 is predicted to increase to 28.8 million, and in 2025 it is predicted to increase to 36 million (BAPENNAS).The increase number of elderly people and changes in quality their life certainly have an impact on life. Changes in life processes and quality of life is closely related to physical activity carried out by an elderly person. Objective: This study aims to identify changes in quality of life in the elderly after being given physical activity interventions and strength exercise with proprioceptive stimulation. Methods: This research is an experimental quasy study with randomized pre and post test group design. Determination of samples based on inclusion criteria until the minimum number of samples was fulfilled. The sample was in one group. Determination of groups using randomize tables then was carried out pre-test in both groups using the WHOQOL-BREF questionnaire The group is given an intervention physical activity strength exercise with proprioceptive stimulation. Physical activity interventions and strength exercise with proprioceptive stimulation were given for 1 month then post-test. Data were analyzed by using paired sample t-test. Result: The data of the study showed the mean value of the Mean ± SD of the quality of life of the respondents in the group before being given physical activity and strength exercise with proprioceptive stimulation of 53.61 ± 3,952, and after being given physical activity and strength exercise with proprioceptive stimulation was equal to 62.00 ± 3,992, with p value (value) that is 0,000 < 0,05. Conclusion: Based on the data above shows that there is an increase in quality of life after physical activity intervention and strength exercise with proprioceptive stimulation